Islamic Historiography and Modernity: A Systematic Literature Review on the Evolution of Muslim Societies in the Postcolonial Era - Al-Shuqairat, Hussein Raja; Al-Maani, Abd-Al Razzak Mahmoud; Aldajah, Mohanad Nayef (Journal of Islamic Thought and Civilization, 2025)
This study examines the evolution of Islamic historiography in response to modernity, analyzing the impact of colonial legacies, socio-political shifts, and epistemological debates. By systematically reviewing 33 peer-reviewed studies, this paper explores historiographical transformations that incorporate indigenous methodologies, decolonial paradigms, and interdisciplinary approaches. The findings emphasize how Islamic historiography engages with contemporary intellectual debates, particularly in the context of inter-imperiality, decolonial theory, and global historiographical discourse. Furthermore, this study highlights the interaction between Islamic historiography and historiographical traditions from other religious and postcolonial perspectives, offering comparative insights into its uniqueness and universality. This research also integrates modern historiographical theories, particularly Hayden White’s narrativism and Reinhart Koselleck’s concept of historical time, to provide a meta-historiographical perspective. Moreover, it underscores the need to expand the scope of Islamic historiography by incorporating quantitative statistical representations, such as frequency analysis of key themes and co-citation networks, thus bridging qualitative and quantitative methodologies. Addressing these dimensions contributes to the academic construction of Islamic historiography, offering practical implications for education, policy-making, and cultural discourse. Additionally, this study emphasizes the role of historiographical synthesis in understanding the evolution of Islamic thought, illustrating how methodological pluralism enhances the field’s analytical depth. By engaging with diverse historiographical frameworks, this systematic review highlights the necessity of integrating historical narratives with contemporary scholarly advancements, ensuring a comprehensive approach to the study of Islamic historiography in modern academia.